2016
DOI: 10.18632/oncotarget.12647
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of promoter of RBL1 enhances the radioresistance of three dimensional cultured carcinoma cells

Abstract: Three dimensional (3D) culture in vitro is a new cell culture model that more closely mimics the physiology features of the in vivo environment and is being used widely in the field of medical and biological research. It has been demonstrated that cancer cells cultured in 3D matrices are more radioresistant compared with cells in monolayer (2D). However, the mechanisms causing this difference remain largely unclear. Here we found that the cell cycle distribution and expression of cell cycle regulation genes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…A similar controversy as to the functional portrait of this atypical cyclin has been presented in the experimental studies. Given the characteristics of the substrates of SCF-cyclin F, the latter might be expected to act as a tumor suppressor, and most experimental studies have recently supported this thesis; however, those supporting its pro-tumorigenic activity also exist [ 12 , 20 , 21 , 22 ]. Although overexpression correlating with a poor prognosis fits better to the best known role of cyclins in human malignancies, it is also well documented that these and virtually all cancer regulatory proteins may manifest oncogenic features in one situation but tumor-suppressive features in another [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar controversy as to the functional portrait of this atypical cyclin has been presented in the experimental studies. Given the characteristics of the substrates of SCF-cyclin F, the latter might be expected to act as a tumor suppressor, and most experimental studies have recently supported this thesis; however, those supporting its pro-tumorigenic activity also exist [ 12 , 20 , 21 , 22 ]. Although overexpression correlating with a poor prognosis fits better to the best known role of cyclins in human malignancies, it is also well documented that these and virtually all cancer regulatory proteins may manifest oncogenic features in one situation but tumor-suppressive features in another [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pan et al showed that different levels of cyclin F, cyclin D and RBL1 between 2D and 3D cultured cells may be associated with radioresistance of cells in 3-dimensional culture. They noted that A549 cells cultured in 3D exhibited lower levels of cyclin F and were less susceptible to G2/M cell cycle arrest after X-ray irradiation ( 25 ). However, the potential role of cyclin F as a tumor-promoting factor and the underlying mechanism remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…It has been revealed that A549 non-small cell lung cancer cells grown on 3D scaffolds were characterized by higher cyclin F expression and were more radio-resistance compared to 2D cultured cells (32). Hepatocellular carcinoma HepG2 cells treated with polysaccharides from abalone had stimulatory potential and exhibited increased mRNA levels of cyclin B, CDK1, and cyclin F and reduced levels of cyclin E and CDK6 (33).…”
Section: Discussionmentioning
confidence: 99%